White Matter Correlates of Cognitive Performance on the UCSF Brain Health Assessment. (26th April 2019) - Alioto, Andrea G.; Mumford, Paige; Wolf, Amy; Casaletto, Kaitlin B.; Erlhoff, Sabrina; Moskowitz, Tacie; Kramer, Joel H.; Rankin, Katherine P.; Possin, Katherine L.
Abstract: Objective: White matter (WM) microstructural changes are increasingly recognized as a mechanism of age-related cognitive differences. This study examined the associations between patterns of WM microstructure and cognitive performance on the University of California, San Francisco (UCSF) Brain Health Assessment (BHA) subtests of memory (Favorites), executive functions and speed (Match), and visuospatial skills (Line Orientation) within a sample of older adults.Method: Fractional anisotropy (FA) in WM tracts and BHA performance were examined in 84 older adults diagnosed as neurologically healthy (47), with mild cognitive impairment (19), or with dementia (18). The relationships between FA and subtest performances were evaluated using regression analyses. We then explored whether regional WM predicted performance after accounting for variance explained by global FA.Results: Memory performance was associated with FA of the fornix and the superior cerebellar peduncle; and executive functions and speed, with the body of the corpus callosum. The fornix–memory association and the corpus callosum–executive association remained significant after accounting for global FA. Neither tract-based nor global FA was associated with visuospatial performance.Conclusions: Memory and executive functions are associated with different patterns of WM diffusivity. Findings add insight into WM alterations underlying age- and disease-related cognitive decline.